2019
DOI: 10.1631/jzus.b1900071
|View full text |Cite|
|
Sign up to set email alerts
|

Catalpol ameliorates LPS-induced endometritis by inhibiting inflammation and TLR4/NF-κB signaling

Abstract: Catalpol is the main active ingredient of an extract from Radix rehmanniae, which in a previous study showed a protective effect against various types of tissue injury. However, a protective effect of catalpol on uterine inflammation has not been reported. In this study, to investigate the protective mechanism of catalpol on lipopolysaccharide (LPS)-induced bovine endometrial epithelial cells (bEECs) and mouse endometritis, in vitro and in vivo inflammation models were established. The Toll-like receptor 4 (TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 38 publications
1
37
0
1
Order By: Relevance
“…Endometrial epithelial and stromal cells were cultured as described in Experiment 1. After LPS treatment for 12 hr (Zhang et al., 2019; Zhu et al., 2015), the medium was collected in a 1.5 ml tube and immediately frozen and stored at − 30°C until the measurement of the concentrations of MCP1, IL‐6, and IL‐8 by ELISA. To normalize the concentration of each chemokine, the cells were harvested and measured the DNA content.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial epithelial and stromal cells were cultured as described in Experiment 1. After LPS treatment for 12 hr (Zhang et al., 2019; Zhu et al., 2015), the medium was collected in a 1.5 ml tube and immediately frozen and stored at − 30°C until the measurement of the concentrations of MCP1, IL‐6, and IL‐8 by ELISA. To normalize the concentration of each chemokine, the cells were harvested and measured the DNA content.…”
Section: Methodsmentioning
confidence: 99%
“…Catalpol, an iridoid glucoside, is extracted from the fresh roots of the traditional Chinese herb Rehmanniae radix preparata. Catalpol shows a wide range of biological activities, like antioxidation, anti-inflammation, anti-cancer, anti-apoptosis, and neuroprotection (Jiang et al, 2015;Yuan et al, 2019;Zhang et al, 2019). Firstly, Liu found that catalpol attenuated atherosclerotic lesions in a rabbit AS model by reducing inflammatory and oxidative stress (Liu and Zhang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, its antioxidant and anti-inflammatory effects were found in a variety of experimental studies in vitro and in vivo [13][14][15][16]. Zhang et al suggested that catalpol alleviated inflammation reactions in LPSstimulated bovine endometrial epithelial cells via the suppression of the TLR4/NF-kB signaling pathway [17]. Catalpol suppressed homocysteineinduced oxidation and inflammation in human aorta endothelial cells [18].…”
Section: Introductionmentioning
confidence: 99%